A Look at Efficient Administration at the Local Level of Nepal - Bagale, Sarmila (DMC Journal, 2024)
This paper aims to explore the limitations of Nepali local governments for effective administration constituted by the provisions of the Nepalese Constitution 2015 for strengthening democracy. Local-level public administration aims to achieve efficiency at all levels, providing necessary public goods and services without discrimination based on affordability. However, there are problems in the LGUs of Nepal. Performance should not only be a cost-benefit analysis but also provide value to citizens. In a scarcely available world, understanding efficiency’s historical perspectives and future role is crucial. Advancements in technology are expected to significantly influence public administration’s evolution. This study collected qualitative data from 5 LGUs in the Kathmandu Valley. A total of 11 in-depth interviews were conducted with representatives and common people from LGUs and 3 federal government officials at both national and local levels. The result shows that there are problems with effective administration at LGUs, which the federal government should address to strengthen the LGs. It delves into understanding that Nepali LGs can deliver services at the local level.